1992
DOI: 10.1016/0037-0738(92)90042-p
|View full text |Cite
|
Sign up to set email alerts
|

Controls on Quaternary coastal evolution of the east-northeastern coast of Brazil: roles of sea-level history, trade winds and climate

Abstract: East-northeastern Brazil has a wave-dominated, micro-to meso-tidal coast, lying entirely within the southern Atlantic trade wind belt. Integration of geologic mapping, radiocarbon dating and vibracoring data shows that the Quaternary coastal evolution of this area was controlled by three major factors: (1) sea-level history; (2) trade winds; and (3) climate change. Sea-level history. Along the east-northeastern coast of Brazil, relative sea level has fallen approximately 5 m during the last 5000 y. Correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
18

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 15 publications
2
70
0
18
Order By: Relevance
“…The sediment source of this canyon system is affected by longshore drifts, which play an important role in distributing sediment on the continental shelf and slope of SE Brazil (Dominguez et al, 1992;Martin and Suguio, 1992). At least three major channel events have been identified within the Rio Doce Canyon system (Fig.…”
Section: Rio Doce Canyon System In the Espírito Santo Basinmentioning
confidence: 99%
“…The sediment source of this canyon system is affected by longshore drifts, which play an important role in distributing sediment on the continental shelf and slope of SE Brazil (Dominguez et al, 1992;Martin and Suguio, 1992). At least three major channel events have been identified within the Rio Doce Canyon system (Fig.…”
Section: Rio Doce Canyon System In the Espírito Santo Basinmentioning
confidence: 99%
“…Because of the remarkable stability observed in the high pressure cell of the South Atlantic, trade winds generated in this cell are expected to show a remarkable persistence during the Quaternary (Dominguez et al 1992). Consequently, these authors conclude to be logical to expect that the patterns of sediment dispersion along the coastal stretch analyzed herein have maintained themselves also persistent during the Quaternary.…”
Section: Discussionmentioning
confidence: 76%
“…Consequently, these authors conclude to be logical to expect that the patterns of sediment dispersion along the coastal stretch analyzed herein have maintained themselves also persistent during the Quaternary. In this sense, using the paleogeographic reconstructions obtained in different coastal plains along the Brazilian East-Northeast coast, Dominguez et al (1992) have shown that, in general, such patterns remained the same since the Pleistocene. In relation to the studied coastal stretch a significant example may be observed in the coastal plain of beach-ridges terraces between the Real and Vaza-Barris rivers, in Sector I (Figs.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations